?GENOTYPE X ENVIRONMENT INTERACTION IN RELATION TO DIALLEL CROSSES FLOWER CHARACTERS IN BEAN (LABLAB PURPUREUS) (Biological Sciences - PJSIR, 2003)
Diallel analysis includes combining ability effects and components of genetic variation. They were estimated over two environments for flower characters from a half-diallel cross by involving six parents. Both general combining ability (gca) and specific combining ability (sca) were important for all characters with preponderance of additive gene actions. Envi- ronment had significant effect on all characters except flowers/inflorescence. Best general combiners were DS52, DS106, DS112 etc. Complete dominance was observed for flowering date in environment-2, flowers/inflorescence in environ- ment-1 and pods/inflorescence in both environments. Over dominance was found for flowering date in environment-1 and partial dominance for flowers/inflorescence in environment-2 and for inflorescence/plant in both environments. Characters were governed by asymmetrical distribution of positive and negative alleles. Dominant and recessive genes were equally distributed for flowering date and inflorescence/plant whereas unequally distributed for flowers/inflorescence and pods/ inflorescence. One or two gene groups were involved in flower characters of lablab bean.